Localised and bifurcating structures in planar shear flows - Wang, Zhe (Nanyang Technological University, 2020)
Turbulent spots in planar shear flows are always accompanied by the presence of (i) the quadrupolar flows outside the spot; and (ii) the counter-rotating streamwise vortices inside the spot. In the present thesis, those flow structures, i.e. quadrupolar flows and streamwise vortices have been treated analytically :